Random Chromosome Partitioning in the Polyploid Bacterium Thermus thermophilus HB27 - Haijuan Li (G3: Genes, Genomes, Genetics, 2019)
Little is known about chromosome segregation in polyploid prokaryotes. In this study, whether stringent or variable chromosome segregation occurs in polyploid thermophilic bacterium Thermus thermophilus was analyzed. A stable heterozygous strain (HL01) containing two antibiotic resistance markers at one gene locus was generated. The inheritance of the two alleles in the progeny of the heterozygous strain was then followed. During incubation without selection pressure, the fraction of heterozygous cells decreased and that of homozygous cells increased, while the relative abundance of each allele in the whole population remained constant, suggesting chromosome segregation had experienced random event. Consistently, in comparison with Bacillus subtilis in which the sister chromosomes were segregated equally, the ratios of DNA content in two daughter cells of T. thermophilus had a broader distribution and a larger standard deviation, indicating that the DNA content in the two daughter cells was not always identical. Further, the protein homologs (i.e., ParA and MreB) which have been suggested to be involved in bacterial chromosome partitioning did not actively participate in the chromosome segregation in T. thermophilus. Therefore, it seems that protein-based chromosome segregation machineries are less critical for the polyploid T. thermophilus, and chromosome segregation in this bacterium are not stringently controlled but tend to be variable, and random segregation can occur.